Os incentivos adversos e a focalizaç\~ao dos programas de proteç\~ao ao trabalhador no Brasil - Ricardo Paes de Barros; Carlos Henrique Corseuil; Miguel Nathan Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– In this paper we evaluate the social programs that deals with worker protection. First we try to show which kind of incentives are induced by these programs. Then we check if the targeting correspond to the poor workers. The programs considered are: abono salarial, seguro-desemprego (unemployment insurance) and Fundo de Garantia do Tempo de Serviço (FGTS). We also discuss issues related to multa pela demiss\~ao sem justa causa (charge for firing), aviso prévio (notification for separation in advance) and período de experiência (trainee period).
Keywords: 330; Arbeitnehmerschutz; Brasilien